Spatial Aspect of Michel Foucault’s Biopolitical Conception - N. N. Orleanskiy (Сравнительная политика, 2015)
Nowadays biopolitics is high on the current political as well as academic agendas. According to Michel Foucault’s biopolitical conception, space loses its previous function as an attribute of power and might and acquires the new one — an encouragement to a human. Space evolves from the location of symbolic authorities’ presence, demonstrated by majestic objects, to the place implementing biopolitical safety technique. Space is a location of threats and benefi ts.